(untitled) (Comprehensive Journal of Science, 2026)
The city of Al-Bayda has witnessed rapid urban development and a haphazard and irregular change in land use patterns. Some lands with different classifications have been encroached upon, and the phenomenon of informal construction began to spread significantly after the fall of the ruling regime in (2011). This paper compares the selected study areas between their condition in 2011 and their condition in (2022). The study concluded with a set of statistical results, noting a significant difference between the area of ​​Al-Bayda in (2011 and 2022). Urban growth has also been irregular, concentrated mainly in the north of the city, with the northeastern axis ranking first, followed by the northwestern axis. This is due to the presence of a good road network and connections that easily link it to the city center and neighboring urban centers. Based on this study, this research arrived at some important recommendations, namely the necessity of sound urban planning to address the increasing population size, the enactment of deterrent laws to prevent unregulated expansion, especially on agricultural lands, and supporting young people by providing multi-family vertical housing complexes through monthly deductions from their salaries. Their salaries (as construction loans) reflect the city’s official policies of sustainable urban planning and development.